(untitled) - Milne, Aileen (London, 2003)
What skills are involved in counselling, and how are they used to help people in personal relationships or the workplace? Readers considering professional help for their problems as well as those interested in counselling as a career will find this revised book indispensable in answering their questions and concerns. It cuts through the theoretical jargon to clearly and thoroughly investigate the field of counselling.
Keywords: Counselling